字典翻译 问答 高中 数学 【一个数学问题ln[(-x-√x^2-a^2)/a^2]+C=ln(-x-√x^2-a^2)+C1C1=C-2lna其中C1=C-2lna怎么来的】
问题标题:
【一个数学问题ln[(-x-√x^2-a^2)/a^2]+C=ln(-x-√x^2-a^2)+C1C1=C-2lna其中C1=C-2lna怎么来的】
问题描述:

一个数学问题

ln[(-x-√x^2-a^2)/a^2]+C=ln(-x-√x^2-a^2)+C1

C1=C-2lna

其中C1=C-2lna怎么来的

林丽华回答:
  由ln[(-x-√x^2-a^2)/a^2]+C=ln(-x-√x^2-a^2)+C1   得ln[(-x-√x^2-a^2)/a^2]-ln(-x-√x^2-a^2)=C1-C   即lna^(-2)=C1-C,   也就是-2lna=C1-C,   所以,C1=C-2lna.
点击显示
数学推荐
热门数学推荐
  • 语文
  • 数学
  • 英语
  • 政治
  • 地理
  • 历史
  • 化学
  • 生物
  • 物理
  • 综合
  • 高考